An automated home-built low-cost fermenter suitable for large-scale bacterial expression of proteins in Escherichia coli. (August 2008) - Riek, Uwe; Tuerk, Roland; Wallimann, Theo; Schlattner, Uwe; Neumann, Dietbert
We have developed an automated fermentation system for cost-efficient upscaling of protein expression in bacteria. The system, built for use by nonbiotechnologists, can be assembled mostly from standard laboratory equipment and allows a largely unattended growth of bacteria to OD 25 (at 600 nm) in a 12 L vessel. The typical yield of 250–350 g of wet weight cell pellet per run, which is equivalent to the biomass obtained from 250 shake flask cultures containing 400 mL Luria-Broth medium each, facilitates the production of large amounts of purified recombinant protein without the laborious need for optimization of expression and purification conditions.